Effect of the competitive growth of Lactobacillus sakei MN on the growth kinetics of Listeria monocytogenes Scott A in model meat gravy. (May 2016) - Quinto, E.J.; Marín, J.M.; Schaffner, D.W.
Abstract: Listeria monocytogenes is a foodborne pathogen capable of growth under refrigeration temperatures. The use of bacteriocin-producing lactic acid bacteria to inhibit Gram-positive pathogen growth may be an important tool to enhance the safety of refrigerated foods. The influence of three different populations of the bacteriocin-producing strain Lactobacillus sakei MN on the growth kinetic parameters of three different populations of L. monocytogenes Scott A co-cultured in model meat gravy at 4, 10, 16, and 22 °C was studied. The Baranyi growth model was used to estimate the kinetic parameters of L. monocytogenes and L. sakei for each strain cultured alone or in co-culture. The highest L. monocytogenes populations were achieved by pure cultures, decreasing in co-culture with the different inocula of L. sakei, at all temperatures. A modified logistic model was applied which includes a factor β that adjusts the effect of L. sakei on L. monocytogenes depending on the environmental conditions. The co-cultures of low (∼1log) L. monocytogenes inocula showed a decrease in β values when temperature increased, indicating that inter-species competition changes with temperature; the 2log- and 4log-inocula of L. monocytogenes co-cultures also showed this behavior but only with the higher initial population of L. sakei . Highlights: The influence of Lactobacillus on Listeria in meat gravy was modeled. The highest L. monocytogenes populations were achieved when no L. sakei was present. L. sakei affected growth of low initial populations of L. monocytogenes . Even if model R 2 values are low, parameter P values are statistically significant. Interspecies competition changes with temperature and with starting concentration.